2023
DOI: 10.3389/fnut.2023.1126579
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on correlation between reactive oxygen species and synbiotics for effective management of ulcerative colitis

Abstract: Ulcerative colitis (UC) is presently considered a multifactorial pathology, which may lead to persistent inflammatory action of the gastrointestinal tract (GIT) because of an improperly managed immunological reactivity to the intestinal microbiota found in the GIT. The immune response to common commensal microbes plays an essential role in intestinal inflammation related to UC synbiotics, and it is an important element in the optimal therapy of UC. Therefore, synbiotics, i.e., a mixture of prebiotics and probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Oxidative stress is a crucial pathological factor that plays an important role in the onset and progression of IBD [23,[35][36][37]. ROS promote mucosal epithelium damage, contributing to mucosal barrier dysfunction [38].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a crucial pathological factor that plays an important role in the onset and progression of IBD [23,[35][36][37]. ROS promote mucosal epithelium damage, contributing to mucosal barrier dysfunction [38].…”
Section: Discussionmentioning
confidence: 99%
“…High fiber diets have been shown to promote the growth of beneficial gut microbiota species, including by increasing bacteria that produce acetate to promote lowered blood pressure and by reducing cardiac remodeling occurring in hypertension and heart failure [ 189 ]. Additional beneficial effects of prebiotics include regulation of weight by reducing obesity, improving glucose tolerance, exerting anti-inflammatory effects, and control of ROS in several inflammatory diseases and cancers [ 190 , 191 , 192 ].…”
Section: Beneficial Dietary Interventions and Therapy To Modulate The...mentioning
confidence: 99%
“…Importantly, ulcerative colitis is often associated with oxidative stress and inflammation. For the therapies of ulcerative colitis, synbiotics could inhibit the oxidative stress’ effects and alleviate the colonic inflammation by lowering the ROS and improving the level of antioxidant enzymes such as catalase, glutathione peroxidase, and superoxide dismutase ( Ashique et al, 2023 ). Moreover, a previous study found that the strong antioxidant properties of cell-free culture supernatant from the Bifidobacterium infantis strain on the skin, might be associated with reduced intracellular ROS and malondialdehyde contents and improved activities of catalase, glutathione peroxidase, and superoxide dismutase as well as upregulation of AQP3 in H 2 O 2 -treated HaCaT cells after treatment ( Ma et al, 2022 ).…”
Section: Role and Regulation Of Aqp3 In Intestinal Oxidative Stress A...mentioning
confidence: 99%